2022
DOI: 10.1101/2022.01.18.476626
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing the impact of roadkill on the persistence of wildlife populations: a case study on the giant anteater

Abstract: Human activity is depleting biodiversity, and road networks are directly contributing to this trend due to roadkill. Nevertheless, few studies empirically estimated the impact of roadkill on wildlife populations. We integrated information on roadkill rates, population abundance, and animal movement to estimate the survival rates and the proportion of the population likely to be extirpated due to roadkill, using giant anteater (Myrmecophaga tridactyla) as model species. We then assessed the consequent implicati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…Roadkill is expected to have a direct impact on species persistence (Borda-de-Água et al, 2011; Grilo et al, 2020), although such effect has been shown only to a handful of species (Ascensão and Desbiez, 2022; Barrientos et al, 2021). Yet, beyond population level effects, its repercussions are likely to exert more profound consequences on ecological networks.…”
Section: Discussionmentioning
confidence: 99%
“…Roadkill is expected to have a direct impact on species persistence (Borda-de-Água et al, 2011; Grilo et al, 2020), although such effect has been shown only to a handful of species (Ascensão and Desbiez, 2022; Barrientos et al, 2021). Yet, beyond population level effects, its repercussions are likely to exert more profound consequences on ecological networks.…”
Section: Discussionmentioning
confidence: 99%